2020
DOI: 10.1021/acsomega.9b04175
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Adsorption Followed by Desorption with Ethanol–Water for Recovery of Penicillin G from Fermentation Broth

Abstract: The hydrophobic adsorption is an alternative to traditional organic solvent extraction for the recovery and purification of Penicillin G (PenG). However, there is a lack of information concerning the effect of process variables and technical feasibility while balancing product degradation. After assessing the integrity of PenG under different conditions, Amberlite XAD-4 was selected from among three different adsorbents. During the batch process using only 0.05 g XAD-4 /mL medium , the adsorption yield increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Researchers have used macroporous resins for the adsorption of several antibiotics. , Jain et al reviewed the use of XAD4 for the adsorption of penicillin, aspirin, ciprofloxacin, etc. In another study by De Barros et al, it was shown that XAD4 had the highest adsorption capacity for recovering penicillin G. Amberlite XAD4 is a nonionic, macroporous styrene-divinylbenzene copolymer. It possesses a relatively high Brunauer–Emmet–Teller (BET) surface area (750.2 m 2 /g), mean pore size (100 Å), pore volume (0.98 mL/g), and a medium pore diameter of 5.58 nm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have used macroporous resins for the adsorption of several antibiotics. , Jain et al reviewed the use of XAD4 for the adsorption of penicillin, aspirin, ciprofloxacin, etc. In another study by De Barros et al, it was shown that XAD4 had the highest adsorption capacity for recovering penicillin G. Amberlite XAD4 is a nonionic, macroporous styrene-divinylbenzene copolymer. It possesses a relatively high Brunauer–Emmet–Teller (BET) surface area (750.2 m 2 /g), mean pore size (100 Å), pore volume (0.98 mL/g), and a medium pore diameter of 5.58 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that maximum penicillin V was recovered within the pH range of 6 to 7 at the given temperature (Figure 2). Studies by De Barros et al 23 suggest that maximum penicillin G recovery could be achieved at pH 4 but requires maintenance of low temperature (4 °C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations